METHODOLOGY FOR TRAINING AND IMPROVING THE EFFICIENCY OF TECHNICAL AND TACTICAL ACTIONS OF FOOTBALL PLAYERS (World Bulletin of Physical Education and Sports Science, 2025)
This article focuses on the use of digital technologies and adaptive training to enhance the technical and tactical preparation of old football players. Training young players using simulations and artificial intelligence tailored to their individual needs improves decision-making speed, reaction, and team play cohesion. This scientific approach positively impacts not only the physical development of young footballers but also their psychological and cognitive growth.
Keywords: Old football players, technical training, tactical training, adaptive training, digital technologies, artificial intelligence, decision-making, simulation, physical development, psychological development, cognitive development, team play.